Coimmobilization of Naringinases on Silk Fibroin Nanoparticles and Its Application in Food Packaging. (14th January 2013) - Wu, Min-Hui; Zhu, Lin; Zhou, Zhen-Zhen; Zhang, Yu-Qing
Abstract : Bombyx mori silk fibroin is a macromolecular biopolymer with remarkable biocompatibility. It was degummed and subjected to a series of treatments, including dissolution and dialysis, to yield an aqueous solution of silk fibroin, which was introduced rapidly into excess acetone to produce crystalline silk fibroin nanoparticles (SFNs), which were conjugated covalently with naringinase using glutaraldehyde as the cross-linking reagent. The SFN naringinases are easily recovered by centrifugation and can be used repeatedly. Naringinase is a bienzyme consisting of α -L-rhamnosidase and flavonoid- β -glucosidase. The enzyme activity and its kinetics were similar to those of the native form, and the optimum reactive temperature for both is 55°C. In our study, centrifugation allowed the separation of enzyme and substrate; after eight cycles the SFN naringinases retained >70% residual activity. The highly efficient processing technology and the use of SFN as a novel vector for a bienzyme have great potential for research and the development of food processing such as the debittering of naringin-containing juices.